Synthesis and Crystal Structure of bis[4-(Imidazol-1-yl)phenyl]methane - Huang, Kun; Du, Bing-Xin; Qin, Da-Bin (Asian Journal of Chemistry, 2014)
A bidentate imidazole derivative with the molecular formula C19H16N4, has been synthesized according to modified Ullmann-type coupling method involving C-N coupling reaction under the catalysis of copper and characterized by the 1H NMR, 13C NMR, elemental analysis and X-ray single-crystal diffraction. In the crystal structure, the two mean plans of benzene rings make dihedral angels of 83.05 (0.07)°. N-H···N hydrogen bonds link the molecules into a 1D supramolecular structure. In addition, weak C-H···p(Ph) stacking interactions are also observed.